Structural and ecophysiological alterations of the water hyacinth [Eichhornia crassipes (Mart.) Solms] due to anthropogenic stress in Brazilian rivers - Vitória,Angela Pierre (2011)
In this work, the structural and ecophysiological alterations (chlorophyll a fluorescence and photosynthetic pigments), and quantification of Cr, Pb and Zn in the leaf limb, petiole and younger and older roots of water hyacinth from the lower, medium and upper Paraíba do Sul river (PSR) and Imbé river were evaluated. The plants from the medium and upper PSR (more industrialized and populated regions) exhibited lower turgid cell in the root cortex, less root hairs and leaf epidermis, chloroplasts with plastoglobules and increased stroma volume. Higher concentrations of metals were observed in the younger and older roots from the medium PSR plants. The results suggested that the plants from more anthropized regions were able to maintain the maximum quantum yield (Fv/Fm) which was a result from the metabolic fitting, increasing the non-photochemical quenching, reducing total chlorophyll/carotenoids and leading to the structural modifications.